An approach to restrict viewing of media - Abd Aziz, Norazah; Mohamad Yusof, Raja Mohamad Fairuz (2015)
Nowadays, the issue of copyright infringement of media contents becomes more vital since the media content is published on the internet for easy access to users.Due to that, the authors’ work affect adversely if their work can be copied or downloaded, modified or shared illegally by unauthorized users.In this paper, we proposed a method to restrict the viewing of images to control the media content accessibility.The method is using basic encryption scheme in order to prevent copyright violations, means, user who does not have specific player and/or with correct password can still view the grey-scale part of the media work in order to accomplish the marketing purposes.The encryption scheme integrates with certain properties such frequency and/or date time which will be used as a salt parameter for Password Based Key Derivation Function 2 (PBKDF2). The method also uses Color Lookup Table (CLUT) as an input to encrypt color table which the decryption process relies on the properties and the correct password.